Tumor-Infiltrating Immune Cells: Triggers for Tumor Capsule Disruption and Tumor Progression? - Jiang, Bin (Ivyspring International Publisher, 2013)
Background: Our previous studies of human breast and prostate cancer have shown that aberrant immune cell infiltration is associated with focal tumor capsule disruption and tumor cell budding that facilitate invasion and metastasis. Our current study attempted to determine whether aberrant immune cell infiltration would have similar impact on colorectal cancer (CRC). Materials and Methods: Tissue sections from 100 patients with primary CRC were assessed for the frequencies of focal basement membrane (BM) disruption, muscularis mucosa (MM) fragmentation, and tumor cell dissemination in epithelial structures adjacent and distal to infiltrating lymphoid aggregates using a panel of biomarkers and quantitative digital imaging. Results: Our study revealed: (1) epithelial structures adjacent to lymphoid follicles or aggregates had a significantly higher (p<0.001) frequency of focally disrupted BM, dissociated epithelial cells in the stroma, disseminated epithelial cells within lymphatic ducts or blood vessels, and fragmented MM than their distal counterparts, (2) a majority of dissociated epithelial cells within the stroma or vascular structures were immediately subjacent to or physically associated with infiltrating immune cells, (3) the junctions of pre-invasive and invasive lesions were almost exclusively located at sites adjacent to lymphoid follicles or aggregates, (4) infiltrating immune cells were preferentially associated with epithelial capsules that show distinct degenerative alterations, and (5) infiltrating immune cells appeared to facilitate tumor stem cell proliferation, budding, and dissemination. Conclusions: Aberrant immune cell infiltration may have the same destructive impact on the capsule of all epithelium-derived tumors. This, in turn, may selectively favor the proliferation of tumor stem or progenitor cells overlying these focal disruptions. These proliferating epithelial tumor cells subsequently disseminate from the focal disruption leading to tumor invasion and metastasis.